APPLICATION OF STRATEGIC MANAGEMENT AS A RISK MANAGEMENT APPROACH IN THE FINANCIAL INDUSTRY - Eriek Alfianza Monde (Scientia Integritas Utama, 2023)
Strategic management will help companies to make the best decisions, assist companies in preventing new problems, increase interaction at all levels, while helping company performance to be more effective, promote healthy and superior competition, and maximize resources. Management strategies are effectively implemented in companies related to financial industry and risk management. In implementing the strategic management process related to risk management, there are several things that must be considered by companies including recognizing the environment, formulating strategies, implementing strategies, and evaluating strategies. This research uses literature study. In obtaining research data, collecting, analyzing and organizing, every article and book obtained as research material. The research method applied is a qualitative method with a type of literature review (literature review) in which the researcher seeks to collect the data obtained and understand the theories from some of the previous literature related to the research. The results of the study show that strategic management is effective in managing risk in the financial industry when the strategic management process can be implemented properly. The risk management process includes: 1. Recognizing the environment in which companies are required to collect, research and provide information as a strategic objective. Indirectly, the introduction of the environment helps to analyze the internal and external teams influencing the company. Financial risk can be minimized if there is sufficient information related to the feasibility of granting credit to prospective customers. This information can be obtained through the prospective customer's business environment through payment ability or liquidity. The information obtained will be analyzed by the credit worthiness section. 2. Formulate a strategy related to determining an action in achieving the goals and objectives of the organization. Companies are required to be able to make decisions that are considered strategic for business progress. Risk management that is not optimal will have an impact on the achievement of short and long term company goals. 3. Implementing a strategy in which the company must be able to create an effective organizational structure to create a comfortable environment. With a clear organizational structure, each employee will have a good job description. Placement of employees in accordance with the specifications on the job description will minimize the financial risk that occurs. This is because employees have good competence in making creditworthiness analysis. 4. Evaluation of the strategy in which the company must evaluate and assess the internal and external environment. Evaluation helps the company to assess the success or failure of the strategy that has been formulated by the company. Evaluation of the creditworthiness of prospective customers will minimize financial risk. Errors in evaluating creditworthiness will result in losses on accounts receivable which will have an impact on company profitability.